An 88-Year-Old Man with Sudden Onset Abdominal Pain - Manouchehrifar, Mohammad; Soltani, Soheil; Ziaei, Sona (Archives of Academic Emergency Medicine, 2018)
An 88-year-old man presented to the emergency department with sudden onset of abdominal pain since 6 hours before. He was a known case of chronic renal failure that underwent hemodialysis three times a week. He also suffered from hypertension and benign prostatic hyperplasia. The patientsâ€™ on-arrival vital signs were as follows: systolic blood pressure: 100/60 mmHg, pulse rate: 88/minute, respiratory rate: 25/minute, oral temperature: 36â—¦C, oxygen saturation 93% in room air. Â He had severely ill appearance on admission. Distended abdomen was considerable but had normal bowel sound and clearly, pain was disproportionate to physical examination. His electrocardiogram showed sinus rhythm and venous blood gas analysis revealed the following: pH=6.96, PaCO2=49 mmHg, HCO3=11 mEq/L, Base excess= -20. Â The bedside ultrasonography showed echogenic particles in hepatic parenchyma and same findings that were passing through the portal vein. Chest and abdominal X-rays were reported as normal. The patient underwent abdominal and pelvic computed tomography (CT) scan with oral contrast. What is your diagnosis?